Effect of Exercise on Quality of Sleep in COVID-19 Patients: A Meta-Analysis - Septyandi Ramadhan; Bhisma Murti; Hanung Prasetya (Journal of Epidemiology and Public Health, 2023)
Background: Coronavirus occurs because the virus lowers the body immune, which can lead to several things such as decreased sleep quality. Gymnastics is one exercise that can improve sleep quality, gymnastics can also reduce stress levels and anxiety. This study aims to discover the effect of gymnastics on sleep quality in COVID-19 patients. Subjects and Method: It was a systematic review and meta-analysis of primary studies. Article searches were conducted based on PICO model eligibility criteria. Population: COVID-19 patients. Intervention: administration of gymnastic intervention. Comparison: no gymnastics intervention. Outcome: improved sleep quality. Article search was conducted through journal databases including Google Scholar, MEDLINE/PubMed, Science Direct, Hindawi, BMC, Europe PMC, and Springer Link using search keywords: "gymnastic", "sleep quality", "gymnastic effect", "exercise", "exercise effect", "COVID-19", "randomized controlled trial", "gymnastic randomized controlled trial", "sleep quality -randomized controlled trial", AND "sleep quality on covid 19". The inclusion criteria used in this study were full paper articles with a Randomized Controlled Trial (RCT), with Odds Ratio (OR) for the effect size. The screened eligible articles were analyzed using RevMan 5.3. Results: This meta-analysis included 9 articles from China, India, South Korea, South America, North America, and Brazil. Good sleep quality increased with gymnastics in COVID-19 patients (aOR= 1.19; 95% CI= 1.14 to 1.24; p<0.001). There was an overestimate publication bias. Conclusion: The administration of gymnastics interventions to COVID-19 patients has a statisti-cally significant effect on improving sleep quality. Keywords: COVID-19, gymnastics, meta-analysis, sleep quality. Correspondence:Septyandi Ramadhan. Master’s Program in Public Health, Universitas Sebelas Maret. Jl. Ir Sutami 36A, Surakarta 57126, Central Java, Indonesia. Email: septyandiramadhan@gmail.com. Mobile: +6281936553398.